2012
DOI: 10.1063/1.4747932
|View full text |Cite
|
Sign up to set email alerts
|

Electronegativity and doping in semiconductors

Abstract: Charge transfer predicted by standard models is at odds with Pauling’s electronegativities but can be reconciled by the introduction of a cluster formation model [Schwingenschlögl et al., Appl. Phys. Lett. 96, 242107 (2010)]. Using electronic structure calculations, we investigate p- and n-type doping in silicon and diamond in order to facilitate comparison as C has a higher electronegativity compared to Si. All doping conditions considered can be explained in the framework of the cluster formation model. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…12 Especially, the higher Pauling electronegativity of dopant materials could enhance the electron density between the dopant ion and the nearest host ions that donate electrons. 13 Here, the electronegativity of tantalum oxide (2.4) is higher than that of titanium oxide (1.59) in a similar oxidation state. Furthermore, extra electrons can be easily generated by increasing the density of Ta 5þ ions whereas the Ti 4þ ions are relatively suppressed.…”
mentioning
confidence: 81%
“…12 Especially, the higher Pauling electronegativity of dopant materials could enhance the electron density between the dopant ion and the nearest host ions that donate electrons. 13 Here, the electronegativity of tantalum oxide (2.4) is higher than that of titanium oxide (1.59) in a similar oxidation state. Furthermore, extra electrons can be easily generated by increasing the density of Ta 5þ ions whereas the Ti 4þ ions are relatively suppressed.…”
mentioning
confidence: 81%
“…Interestingly, from Figure e, the adsorption energies of the OH/M-doped ZnO(0001) and the <EBO> of M–O bonds increase with an increase in the ions’ electronegativity of dopants in this work, demonstrating that doping with lower electronegativity metallic ions can decrease the covalency level of the bonds between the OH groups and ZnO slabs and result in the limited adsorption of OH groups on ZnO. Because when ZnO is doped by lower electronegativity metallic ions, the electrons will transfer from dopants to the nearest neighbor host atoms, leading to the formation of p-type oxides (acceptor). , Besides, the investigation of Cu/M-doped SnO 2 interfaces demonstrated that the hole carriers provided by the p-type SnO 2 (low-valence doping) would recombine with the electrons provided by the metal, leading to stronger interfacial bonding and interface adhesion . As opposed to Cu, which tends to lose electrons, the OH groups tend to gain electrons; thus, the OH groups would prefer to adsorb on the n-type ZnO (higher electronegativity dopants) rather than the p-type ZnO (lower electronegativity dopants).…”
Section: Resultsmentioning
confidence: 62%
“…Because when ZnO is doped by lower electronegativity metallic ions, the electrons will transfer from dopants to the nearest neighbor host atoms, leading to the formation of p-type oxides (acceptor). 56,57 Besides, the investigation of Cu/M-doped SnO 2 interfaces demonstrated that the hole carriers provided by the p-type SnO 2 (low-valence doping) would recombine with the electrons provided by the metal, leading to stronger interfacial bonding and interface adhesion. 58 As opposed to Cu, which tends to lose electrons, the OH groups tend to gain electrons; thus, the OH groups would prefer to adsorb on the n-type ZnO (higher electronegativity dopants) rather than the p-type ZnO (lower electronegativity dopants).…”
Section: Effect Of Doping On Electronic Structurementioning
confidence: 99%
“…Moreover, according to the cluster formation model, thallium with the electronegativity of 1.62 against aluminum with 1.61 can result in a cluster system of TAZO with a higher possibility of electron donation than AZO. [30][31][32][33]…”
Section: Introductionmentioning
confidence: 99%